Evaluation of the Acid Baking Technique to Decrease the Phosphorus Content of the Iron Ore - Silva,Leonardo Martins da (2019)
Unlike the available mineral resources, the steelmaking processes have demanded raw material with lower phosphorus content to decrease the costs, energy use, and the residue generated within the steel plant. One alternative is to develop pretreatment of the iron ore concentrates producing raw materials with lower phosphorus. Depending on the mineral structure, a heat treatment combined with leaching could be an efficient way to achieve concentrates with low phosphorus (less than 0.01%), suitable for steelmaking processes. A fast and efficient way of applying energy to iron ore particles is the use of microwave to heat the particles. Thus, we propose a treatment using microwave heating while mixing with a dilute aqueous solution of sulfuric acid, followed by quenching during leaching with water, as a feasible route for the phosphorus removal from iron ore particles. We performed a design of experiment (DOE) to investigate the optimal conditions of heating and leaching, which maximize the rate of phosphorus removal. The structure of the iron ore particles after their treatment with microwave energy was observed by scanning electron microscopy (SEM). Thus, we analyze the optimal conditions for heating and leaching, the structure of the iron ore particles and which mechanism and rate equations are controlling the phosphorus removal. The results indicated that the average heating time is 10 min, the size of the crack of the order of 20µm and a leaching time of 8 min are adequate to achieve less than 0.01% of phosphorus. We demonstrated that under the most favorable combination of conditions for heating followed by leaching proposed in this study, the removal of the phosphorus content in the iron ore samples could reach 100%.